Application of direct steam injection system to minimize browning of white radish (Raphanus sativus) broth during sterilization - Ham, Tae Hoon; Yoon, Won Byong (International Journal of Agricultural and Biological Engineering, 2017)
Direct steam injection (DSI) was applied to minimize the quality changes of white radish (Raphanus sativus) broth during sterilization. This study compared the degree of browning of white radish broth from a retort sterilization system and a DSI system. The quality changes after thermal treatments, such as retorting and DSI, were evaluated by Lab color values, the browning index (BI) and sensory evaluation. As the volume of the retort pouch increased, the thermal processing time increased. Significant increases of a and b values, color difference and BI were observed. Unlike the retort sterilization, the DSI treatment showed no significant differences in color properties of the radish broth with a wide range of sterilization temperature. The highest sensory score among the DSI treated samples was observed at the lowest sterilization temperature (125°C). The results demonstrated that the DSI treatment showed a higher stability in the quality associated with the browning reaction, such as the color indices and BI because the DSI process rapidly increased the temperature of the radish broth by transferring the latent heat of steam to the fluid.Keywords: direct steam injection (DSI), retort, sterilization, quality, browning, white radish broth, sensory evaluationDOI: 10.25165/j.ijabe.20171006.3350Citation: Ham T H, Yoon W B. Application of direct steam injection system to minimize browning of white radish (Raphanus sativus) broth during sterilization. Int J Agric & Biol Eng, 2017; 10(6): 210–220.